2020
DOI: 10.3847/1538-4365/ab6610
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Early Evolution of a Slow Coronal Mass Ejection Imaged by the Parker Solar Probe

Abstract: During its first solar encounter, the Parker Solar Probe (PSP ) acquired unprecedented up-close imaging of a small Coronal Mass Ejection (CME) propagating in the forming slow solar wind. The CME originated as a cavity imaged in extreme ultraviolet that moved very slowly (< 50 km/s) to the 3-5 solar radii (R ) where it then accelerated to supersonic speeds. We present a new model of an erupting Flux Rope (FR) that computes the forces acting on its expansion with a computation of its internal magnetic field in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 57 publications
4
45
0
Order By: Relevance
“…This interpretation is consistent with other studies of the streamer belt wind during PSP Encounter 4, for example, Badman et al (2020b) found a reduced magnetic flux during this period that did not fit the general radial scalings seen in the rest of the PSP data. The inferred streamer belt wind width is also consistent with coronal images that show the streamer rays to have a width of around 10 • to 20 • , which is likely a slight overestimate due to the line-of-sight integration (Rouillard et al 2020;Poirier et al 2020).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This interpretation is consistent with other studies of the streamer belt wind during PSP Encounter 4, for example, Badman et al (2020b) found a reduced magnetic flux during this period that did not fit the general radial scalings seen in the rest of the PSP data. The inferred streamer belt wind width is also consistent with coronal images that show the streamer rays to have a width of around 10 • to 20 • , which is likely a slight overestimate due to the line-of-sight integration (Rouillard et al 2020;Poirier et al 2020).…”
Section: Discussionsupporting
confidence: 81%
“…Much of the solar wind measured in the early PSP solar encounters has been of open-field coronal hole origin (Bale et al 2019;Panasenco et al 2020;Badman et al 2020a,b), although short periods of streamer belt wind near the heliospheric current sheet (HCS) were also identified (Szabo et al 2020;Rouillard et al 2020;Lavraud et al 2020). Encounter 4, however, was different in that for the majority of the outbound portion, PSP was consistently in streamer belt plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 2, we present an example six-hour interval from after perihelion during PSP's second encounter. During this encounter, PSP primarily measured slow Alfvénic wind with complicated solar source mapping (Rouillard et al 2020). .…”
Section: Resultsmentioning
confidence: 99%
“…The longitudinal extent of the CME is certainly greater than its latitudinal extent. Using the CME reconstruction of Rouillard et al (2020) and assuming that the flux rope was horizontal (east-west oriented), a successful interpretation of its aspect both in STA/C2 images and in situ could be achieved (see McComas et al 2019). The CME reconstruction of interest here gives an angular separation between the eastern and western flank of about 85°at 06:00 UT on DOY 315.…”
Section: The Cme Of 2018 November 10-12mentioning
confidence: 99%
“…Assuming that the CME moved almost directly toward PSP, this suggests that the magnetic field lines associated with the magnetic field measured in situ by PSP all connect to the CME throughout the duration of the SEP event. In Figure 3 we use the CME 3D reconstruction model presented in Rouillard et al (2020) and applied to the present CME (McComas et al 2019) to determine the CME position and extent in 3D. The PSP orbit is shown at 04:08 UT on DOY 315.…”
Section: The Cme Of 2018 November 10-12mentioning
confidence: 99%